1985
DOI: 10.1007/bf00401177
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies to plant growth regulators. II. Indole-3-acetic acid

Abstract: The production and characterization of high-affinity monoclonal antibodies suitable for the radio- and enzymeimmunoassay of the endogenous plant growth regulator, indole-3-acetic acid (IAA), is reported. Hybridomas were produced by fusion of NS 1 myeloma cells with spleen cells from Balb/c mice immunized with IAA-bovine serum albumin conjugates. From an initial collection of 158 wells containing cells secreting monoclonal antibodies against IAA, seven were used to derive cell clones. Three of these are describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
28
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 8 publications
4
28
0
Order By: Relevance
“…As shown in Figure 3 such deviations could not be observed in the test extract. Together with the data shown in Figure 2, the results show that combination of separation techniques with ELISA (17) and IAA (18). In these studies, it became clear that the selection of mAB with specificities rivaling or even surpassing those of antisera is possible.…”
Section: -(2-ethylhexylamino)-2-methylpyrollo-[23-d]-pyrimidine and supporting
confidence: 57%
See 2 more Smart Citations
“…As shown in Figure 3 such deviations could not be observed in the test extract. Together with the data shown in Figure 2, the results show that combination of separation techniques with ELISA (17) and IAA (18). In these studies, it became clear that the selection of mAB with specificities rivaling or even surpassing those of antisera is possible.…”
Section: -(2-ethylhexylamino)-2-methylpyrollo-[23-d]-pyrimidine and supporting
confidence: 57%
“…In these studies, it became clear that the selection of mAB with specificities rivaling or even surpassing those of antisera is possible. It was furthermore shown that, by employing appropriate screening protocols, the selection of high affinity mAB is possible (17,18). Both specificity and affinity need to be maximized in order to allow for optimum immunoassay performance.…”
Section: -(2-ethylhexylamino)-2-methylpyrollo-[23-d]-pyrimidine and mentioning
confidence: 99%
See 1 more Smart Citation
“…To raise an antibody against IAA, it must be coupled to a carrier protein. The nitrogen in the indole ring (IAA-N), [9][10][11] the carboxyl group (IAA-C), 12,13) and the hetero atoms introduced on a benzene ring of IAA (IAA-H) 14,15) are often used for the conjugation. The antibodies raised against IAA-C showed higher and wider cross-reactivity to IAA conjugates than the antibodies against IAA-N or IAA-H, and required methylation of samples for the analysis of free IAA in plants.…”
mentioning
confidence: 99%
“…We report here the development of an indirect competitive ELISA for the quantitation of extensin precursors. This type of ELISA has been demonstrated to be useful and sensitive in the assay of important biological molecules (10). ' Deglycosylation of P1 and P2 involved HF solvolysis of the saccharide component using anhydrous HF with 10% methanol as the scavenger for 1 h at 0°C (12).…”
mentioning
confidence: 99%